Analysis of Cinnamomum Land Suitability and The Conservation Efforts at Eka Karya Bali Botanic Garden - Ayyu Rahayu (Fakultas Pertanian Universitas Padjadjaran, 2020)
Cinnamomum is an aromatic plants that have high economic value. At the Eka Karya Bali Botanic Garden Plant Conservation Center, the Cinnamomum collection has a problem, that is drought and deciduous leaves. The purpose of this study is to determine the land suitability class and climate of the growth of Cinnamomum collections. The method used is by matching the Cinnamomum growth conditions data to the actual data on the condition of the land. The results show that the level of land suitability for Cinnamomum collections is S3 (marginally suitable) with a limiting factor is water availability. Strategies that can be used to reduce the impact of excess water are water management and the application of organic matter.